Mental Health Literacy Among Older Adults in Bangkok - Koistinen, Nutwadee; Boonyamalik, Plernpit; Amnatsatsue, Kwanjai (Journal of Public Health Nursing, 2025)
This cross-sectional descriptive study aimed to examine mental health literacy and its predictive factors among community-dwelling older adults living in the Bangkok Metropolitan area. A total of 370 individuals, including both males and females aged 60 years and above, were recruited from 8 communities in Bangkok using a multi-stage sampling method. Data were collected by a researcher using a 6-part questionnaire, with CVI value greater than 0.8 and acceptable Cronbach’s alpha of 0.75-0.86. The findings revealed that most subjects were female (67.6%), aged between 60-69 years old (54.6 %), married (53.5%). Most subjects had primary school education (60.3 %), and got diagnosed of Hypertension (60.5 %). According to Pearson product-moment correlation, a positive relationship between mental health literacy and social support (r = 0.495), access to health services (r = 0.397), and family relationships (r = 0.371). Nevertheless, there was a negative correlation between depression and mental health literacy (r = -0.132). In addition, Multiple linear regression revealed that access to health services and social support could jointly explained 32.1% of the variation in mental health literacy among older people at p-value < 0.001. The findings of this study can be utilized to develop nursing services that enhance mental health literacy among elderly individuals in Bangkok. Focus should be placed on improving social support and increasing accessibility to health services in order to promote healthy mental well-being.